Mycoplasma pneumoniae and Schistosoma mansoni co-infection in a young patient with extensive longitudinal acute transverse myelitis - Hassan Ali Alayafi; Mubarak Alruwaili; Talal Khalid Aljumah; Ali Alshehri; Deema Alrasheed; Muhannad Faleh Alanazi; Raed AlRuwaili; Naif H Ali; Anas Mohammad Albarrak; Barakat M AlRashdi; Ahmed E Taha (Journal of Infection in Developing Countries)
Introduction: Acute transverse myelitis is an uncommon inflammatory, intramedullary, disorder of the spinal cord. Spastic paraplegia, impaired sphincter functions, and sensory loss, with sensory level, are the clinical manifestations of this devastating disorder. The utilization of magnetic resonant imaging (MRI) contributes to the surge in the diagnosis of more ATM cases. Although the causes of ATM are numerous, both Mycoplasma pneumoniae and Schistosoma mansoni are uncommon causes and their co-existence in the same patient has not been reported before in Saudi Arabia.